Duty Rosters and Workloads of Obstetricians in Germany: Results of a Germany-wide Survey - Neimann, Johannes; Knabl, Julia; Puppe, Julian; Bayer, Christian Michael; Gass, Paul; Gabriel, Lena; Seelbach-Goebel, Birgit; Lermann, Johannes; Schott, Sarah (Geburtshilfe und Frauenheilkunde, 2017)
Background Compiling a daily hospital roster which complies with existing laws and tariff regulations and meets the requirements for ongoing professional training while also taking the legal regulations on the health of employees into account makes planning the duty roster a challenge. The aim of this study was to obtain a realistic picture of existing duty roster systems and of the current workloads of obstetricians in Germany.Method This online survey was sent to 2770 physicians training to become obstetricians or specializing in specific areas of obstetric care. The survey consisted of an anonymized 95-item questionnaire which collected data on different types of duty roster systems and the workload of obstetricians in Germany for the period from 17.02.2015 to 16.05.2015.Results Out of a total of 2770 physicians who were contacted, 437 (16%) completed the questionnaire. Across all forms of care, the care provided outside normal working hours usually (75%) consisted of a combination of regular working times and on-call duty or even consisted entirely of standby duty. Level I perinatal centers were most likely 20% (n = 88) to have a shift system in place. Working a shift system was significantly more common in care facilities which had previously carried out a job analysis. The number of physicians in hospitals who are present during the night shift was higher in facilities with higher numbers of births and in facilities which offered higher levels of care. In addition to regularly working overtime and the fact that often not all the hours worked were recorded, it was notable that the systems used to compile duty rosters often did not comply with legal regulations or with collectively agreed working hours nor were they compatible with the staff planning requirements.Outlook The results of this study show that the conditions of work, the working times, and the organization of working times in obstetric departments are in need of improvement. Recording the actual times worked together with an analysis of the activities performed during working times and while on standby would increase the level of transparency for employers and employees.Hintergrund Die Umsetzung einer gesetzes- und tarifkonformen Tagesplanung im Krankenhaus im Einklang mit einer kontinuierlichen Weiterbildung unter Berücksichtigung der vorgeschriebenen Regelungen zum Gesundheitsschutz von Arbeitnehmern stellt die Dienstplanung vor Herausforderungen. Ziel der vorliegenden Untersuchung ist es, ein realitätsnahes Bild der vorherrschenden Dienstmodelle und der derzeitigen Arbeitsbelastung von in der Geburtsmedizin tätigen Ärzten in Deutschland zu generieren.Methode Diese Onlineerhebung wurde an 2770 Ärzte in Facharzt- und Schwerpunktweiterbildung versandt. Sie erfasst mit einem anonymisierten 95-Item-Fragebogen verschiedene Dienstmodelle und die Arbeitsbelastung von geburtshilflich tätigen Ärzten in Deutschland im Zeitraum vom 17.02.2015 bis 16.05.2015.Ergebnisse Von 2770 ärztlichen Adressaten lagen 437 (16%) Antwortbögen vor. Über alle Versorgungsformen hinweg wird der Dienst außerhalb der Regelarbeitszeit am häufigsten (75%) in einer Kombination aus Regeldienst und Bereitschaftsdienst (BD) bzw. reinem BD organisiert. Ein Schichtsystem ist mit 20% (n = 88) am häufigsten in Perinatalzentren Level I etabliert. Es wird signifikant häufiger in Schichtdienst gearbeitet, wenn zuvor eine Arbeitszeitanalyse vorgenommen wurde. Die Anzahl der im Nachtdienst im Krankenhaus anwesenden Ärzte nimmt bei höherer Geburtenzahl sowie höherer Versorgungsstufe zu. Neben regelmäßigen Überstunden und oft inkompletter Arbeitszeiterfassung fällt insbesondere auf, dass die Dienstmodelle oft weder mit den gesetzlichen und tariflichen Regelungen noch mit den tatsächlichen Anforderungen an die Personalplanung vereinbar sind.Ausblick Die vorliegenden Ergebnisse zeigen verbesserungsbedürftige Zustände in Bezug auf die Arbeits- und Dienstsituation sowie -organisation in geburtshilflichen Abteilungen. Insbesondere eine Erfassung der Arbeitszeit und Tätigkeitsanalysen im Dienst würden die Transparenz für Arbeitgeber und -nehmer erhöhen.
Keywords: workload; specialization; obstetrics; work-life balance; duty roster; perinatal center